Enabling Fast‐Charging Lithium‐Ion Battery Anodes: Influence of Spheroidization on Natural Graphite. Issue 7 (6th April 2022) - Mancini, Marilena; Martin, Jan; Ruggeri, Irene; Drewett, Nicholas; Axmann, Peter; Wohlfahrt‐Mehrens, Margret
Abstract: Excellent fast‐charging performance is a key requirement for lithium‐ion batteries intended for automotive applications. Rational particle design for active materials within electrodes represents a strategic approach to minimize kinetic limitations – especially for the anode, where the lithium intercalation rate affects the overall cell charging capacity at elevated current densities. Typically, for practical applications, natural graphite flakes are shaped into rounded particles via a mechanical spheroidization process. In this work, we show that both surface and bulk particle properties correlate strongly with the applied spheroidization conditions, and directly affect the electrochemical performance, particularly in terms of lithium‐intercalation rate. We demonstrate that graphite particles with a surface rich in prismatic planes, structural defects, and oxygen‐rich groups are favorable for fast lithium uptake. The influence of the graphite particle characteristics on the lithium intercalation rate plays a key role at the electrode and cell level, affecting the overall cell performance. We provide new insights into particle optimization during spheroidization as an effective strategy for developing fast‐charging lithium‐ion batteries. Abstract : Round and fast : During the shaping process of natural graphite flakes into rounded particles, process parameters control surface and bulk properties of the product. Direct correlation between graphite surface characteristics and Li‐intercalation rate is identified. Tailoring of particle shape and carbon surface properties allows optimization of both electrode design and active material functionality for fast‐charging applications.